(untitled) (Itinera, 2024)
In the early modern period, St. Paul’s moral injunction (Rom. 11.21) mḕ hypsēlophrónei allà phoboû, noli altum sapere, sed time («be not highminded, but fear») was often distorted as if it meant «you should not know high things» and was interpreted as a warning against intellectual knowledge. In reality, Saint Paul’s admonition recalls some traditional Greek commonplaces such as self-knowledge and thinking mortal thoughts. Furthermore, already the ancient experience of the hypsēlophroneîn couples the moral meaning with the intellectual one, but also includes an aesthetic dimension effectively illustrated by the rhetoric of sublime (as attested by Philo of Alexandria and especially by Longinus).